Safety and feasibility of one-stage neonatal approach for short-segment Hirschsprung’s disease - Quynh Anh Tran; Hien Duy Pham; Dung Boi Ly; Minh Quang Ngo; Nhung Thi Nguyen; Liem Thanh Nguyen; Quang Thanh Nguyen (PLoS ONE, 2026)
Background Early definitive surgery for Hirschsprung disease (HD) in neonates is increasingly adopted to reduce preoperative morbidity and preserve long term bowel function. However, comparative data across minimally invasive approaches in neonates with short segment disease remain limited. This study compared outcomes of single incision laparoscopic assisted endorectal pull through (SILEP), conventional laparoscopic assisted endorectal pull through (CLEP), and complete transanal endorectal pull through (TERPT) for rectosigmoid HD. Methods We conducted a retrospective cohort study of 55 neonates who underwent one stage definitive surgery before 28 days of age at a high volume center between January 2019 and December 2021. The primary outcome was long term bowel function assessed using the Rintala Bowel Function Score (BFS) after a minimum of 4 years of follow up. Secondary outcomes included operative parameters, postoperative complications (Clavien Dindo classification), and cosmetic outcomes using the Manchester Scar Scale (MSS) in the laparoscopic groups. Results All patients successfully underwent surgery at a mean age of 22.4 ± 4.3 days. Operative time differed across approaches and was shorter for SILEP (53.8 ± 11.9 minutes) and TERPT (52.1 ± 18.3 minutes) than for CLEP (70.2 ± 22.5 minutes, p = 0.036). At follow up (mean 54.0 ± 7.7 months), the overall BFS was 17.5 ± 2.5 with no significant differences among groups (p = 0.32). MSS was numerically lower for SILEP than for CLEP (6.2 ± 1.1 vs 6.8 ± 1.9, p = 0.53). Complications were infrequent, with 14 minor and 7 major events, and there was no mortality or Clavien Dindo grade IV or V morbidity. Conclusion SILEP, CLEP, and TERPT are feasible one stage options for neonates with rectosigmoid HD, with comparable long term bowel function and low rates of major complications. SILEP and TERPT were associated with shorter operative times, and SILEP showed a trend toward improved cosmetic scores compared with CLEP. These findings support an individualized approach to technique selection based on intraoperative requirements and institutional expertise.